Adopsi Anak dalam Teologi Kristen : Opini Jemaat HKBP Kana Resort Kana Duri (Jurnal Pendidikan Agama dan Teologi, 2025)
This study discusses child adoption in the context of Christian theology, focusing on the opinions of the congregation of HKBP Kana Resort Kana Duri. Child adoption is an effort to provide affection and protection to children who do not have biological parents or who have been abandoned, in accordance with the values of love and acceptance taught in the Bible. In the Christian view, adoption is not only seen as a social solution, but also has a deep theological dimension, reflecting the relationship between God and His people as Father and His children. This study uses a qualitative descriptive approach to explore the congregation's views on child adoption and the challenges they face in implementing this practice. Data were collected through interviews, observations, and literature studies, which were then analyzed to understand the theological meaning of child adoption and the congregation's opinions on adoption. From the results of the study, it can be concluded that the problems that exist are in the personal and social readiness of the congregation, lack of education, and the absence of special assistance from the church as an institution of faith that should be a protector and director in making ethical and moral decisions for its congregation.